A case of esophageal carcinoma on esophageal varices treated by endoscopic submucosal dissection after endoscopic injection sclerotherapy. Issue 1 (30th December 2022) - Nakachi, Kenichiro; Maekita, Takao; Deguchi, Hisanobu; Kimura, Masatomo; Iguchi, Mikitaka; Yoshida, Satoshi; Kitano, Masayuki
Abstract: Esophageal varices (EVs) are often treated using endoscopic injection sclerotherapy. Endoscopic submucosal dissection (ESD) has been used for early esophageal epithelial neoplasia worldwide. We report a case of early esophageal squamous cell carcinoma (ESCC) that occurred over EVs, in which the EVs were treated with endoscopic injection sclerotherapy before the early ESCC was treated with endoscopic submucosal dissection. Argon plasma coagulation was finally performed to prevent the recurrence of varices. No serious complications, such as severe bleeding or perforation, were observed. Histopathological examination revealed submucosal veins occluded with an organized thrombus for which endoscopic injection sclerotherapy with an intravariceal injection of sclerosant had been performed, but no fibrosis was observed outside the blood vessels. This explains that the injected sclerosant into EVs did not cause any tissue reaction like fibrosis in the submucosa surrounding the vein, which may have made endoscopic submucosal dissection safer and easier. Varices have not recurred, and ESCC has also not recurred for 5 years. We demonstrated a successful treatment of ESCC on EVs and no submucosal fibrosis other than inside the occluded vessels and verified it histologically.